Moisture Regime Influencing Different Fractions of Applied Phosphorus in Calcareous Soil of North Bihar - Vidyarthi, R.P.; Kumar, Amrendra; Chaurasia, Jageshwar; Chaurasia, Arunchal (Asian Journal of Chemistry, 2010)
The soil under study was of calcareous in nature baving 30% calcium carbonate. Fractionation of different inorganic bound P in soil viz AI-P and occ. AI-, Fe-P occ. Al-P and Ca-P periodically followed the weathering sequence of Ca-P > occ. Fe-P> Fe-P which is expected of young alluvium soil of calcareous origin. Neither Al-P nor occ Fe-P, Al-P was detected in the soil under both the situations, i.e., at field capacity and water logged condition irrespective of change in incubation period or levels of P2O5 applied.